CuI/Fe3O4 NPs@Biimidazole IL‐KCC‐1 as a leach proof nanocatalyst for the synthesis of imidazo[1, 2‐a]pyridines in aqueous medium. (20th October 2020) - Azizi, Sajjad; Shadjou, Nasrin; Soleymani, Jafar
Abstract : In the present work, an innovative leach proof nanocatalyst based on dendritic fibrous nanosilica (DFNS) modified with ionic liquid loaded Fe3 O4 NPs and CuI salts was designed and applied for the rapid synthesis of imidazo[1, 2‐ a ]pyridines from the reaction of phenyl acetylene, 2‐aminopyridine, and aldehydes in aqueous medium. The structure of the synthesized nanocatalyst was studied by field emission scanning electron microscopy (FESEM), transmission electron microscopy (TEM), Fourier transform infrared (FT‐IR), flame atomic absorption spectroscopy (FAAS), energy‐dispersive X‐ray (EDX), and X‐ray diffraction (XRD), vapor–liquid–solid (VLS), and adsorption/desorption analysis (Brunauer–Emmett–Teller [BET] equation) instrumental techniques. CuI/Fe3 O4 NPs@IL‐KCC‐1 with high surface area (225 m 2 g −1 ) and porous structure not only exhibited excellent catalytic activity in aqueous media but also, with its good stability, simply recovered by an external magnet and recycled for eight cycles without significant loss in its intrinsic activity. Higher catalytic activity of CuI/Fe3 O4 NPs@IL‐KCC‐1 is due to exceptional dendritic fibrous structure of KCC‐1 and the ionic liquid groups that perform as strong anchors to the loaded magnetic nanoparticles (MNPs) and avoid leaching them from the pore of the nanocatalyst. Green reaction media, shorter reaction times, higher yields (71–97%), easy workup, and no need to use the chromatographic column are the advantages of the reported synthetic method. Abstract : An innovative leach proof nanocatalyst based on dendritic fibrous nanosilica (DFNS) modified with ionic liquid loaded Fe3 O4 NPs and CuI salts was designed and applied for the rapid synthesis of imidazo[1, 2‐ a ]pyridines from the reaction of phenyl acetylene, 2‐amino pyridine, and aldehydes in aqueous medium.